Promotional effect of niobium substitution on the low-temperature activity of a WO3/CeZrOx monolithic catalyst for the selective catalytic reduction of NOx with NH3. Issue 75 (10th October 2017) - Xu, Haidi; Lin, Qingjin; Wang, Yun; Lan, Li; Liu, Shuang; Lin, Chenlu; Wang, Qin; Wang, Jianli; Chen, Yaoiqng
Abstract : Optimal WO3 substituted by Nb2 O5 could obviously improve the low-temperature NH3 -SCR activity of WO3 /Ce0.68 Zr0.32 O2, and the Nb-substituted catalyst showed excellent SO2 and H2 O tolerance could be a promising candidate for NH3 -SCR catalyst. Abstract : A series of Nb-substituted WO3 /CeZrO x catalysts were prepared by the co-impregnation method and applied in the selective catalytic reduction of NO x with NH3 (NH3 -SCR). NH3 oxidation, N2 sorption, XRD, Raman, UV-vis, XPS, H2 -TPR, O2 /NH3 -TPD and in situ DRIFTS were performed to correlate the redox property and surface acidity to NH3 -SCR performance of Nb-substituted catalysts. The catalyst with 5 wt% substitution amount of Nb2 O5 presented excellent deNO x activity and N2 selectivity in a broad reaction temperature window of 190–434 °C at a gas space velocity of 30 000 h −1 . The characterization results demonstrated that the partial substitution of WO3 by Nb2 O5 not only led to strong redox properties arising from abundant surface active oxygen species, but also promoted the adsorption of NH3 and the redistribution of acid sites due to Nb–OH related to Brønsted acid sites and NbO bonded to strong Lewis acid sites. The enhancement of surface active oxygen species and Brønsted acid sites promoted the low-temperature (below 250 °C) deNO x activity. However, the preoxidation of NH3 at high temperatures slightly suppressed the NO x conversion of the catalyst with more strong Lewis acid sites at above 400 °C. Moreover, the catalyst also showed excellent sulfur tolerance and could be a promising candidate for practical applications in NO x abatement.